Characteristics Quality Sensory and Chemical of Cincalok Rebon Shrimp (Acetes eryhraeus) Made Using the Method Backslopping - Stefani Rani Audina; Bustari Hasan; Tjipto Leksono (Fakultas Perikanan dan Kelautan, Universitas Riau, 2020)
This study aims to determine the duration of the fermentation process, and aims to determine the effect of the addition of the substrate from the previous fermentation on the sensory quality and chemical properties of the chopped rebon shrimp made by the Backslopping method. The study method used was experimental with a fully randomized design (CRD). With 4 treatment levels, namely the addition of substrate 0%, 10%, 15% and 20%, the percentage is calculated based on the weight of the shrimp reconstruction. The results showed that the addition of substrate to the cincalok fermentation product had a significant effect on the organoleptic values (appearance, aroma, taste and texture), pH, NPN and amino acids. The best treatment is 20% with the characteristics of attractive appearance, bright light pink color and not pale; it does not smell fishy and has a characteristic sour aroma of cincalok fermentation; it has a slightly salty taste and a sour taste, the texture is firm and slightly runny. The 20% treatment has a pH value of 3.5 during the 5 day fermentation period, the NPN value is 10.05%, the water content is 68.50%, the ash content is 9.67%, the fat content is 1. 46%, the protein content is 35.27, the carbohydrate content is 7.53% and the higher the substrate is added, the feed is more high sugar content 11.10%, arginine 5.93%, leucine 7.88 and low glycine content 2.93%.